2006
DOI: 10.3989/gya.2006.v57.i4.64
|View full text |Cite
|
Sign up to set email alerts
|

HPLC evaluation of the minor lipid components of by-products resulting from edible oil processing

Abstract: RESUMEN Evaluación por HPLC de componentes lipídicos minoritarios de subproductos de la refinación de aceites comestiblesEl trabajo realiza una evaluación analítica de algunos subproductos resultantes del la refinación de aceites comestibles. Las muestras procedieron de 4 plantas que aplicaban refinación química. Después de un pretratamiento de las muestras estas se sometieron a un análisis cromatográ-fico para el aislamiento y derivatización de los siguientes componentes minoritarios: esteroles libres y acila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Additionally, it contains material with some commercial value (Dumont and Narine, 2008;Garcia-Zapateiro et al, 2010;Verleyen et al, 2001;El-Mallah et al, 2006) as animal feed ingredient (Nang et al, 2009;Haslenda and Jamaludin, 2011). Several methods have been proposed to recover phytosterols from the deodorizer distillate VerleyenVerhe, 2001;Kasim et al, 2010;Fabian et al, 2009).…”
Section: Fatty Acid Distillatementioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, it contains material with some commercial value (Dumont and Narine, 2008;Garcia-Zapateiro et al, 2010;Verleyen et al, 2001;El-Mallah et al, 2006) as animal feed ingredient (Nang et al, 2009;Haslenda and Jamaludin, 2011). Several methods have been proposed to recover phytosterols from the deodorizer distillate VerleyenVerhe, 2001;Kasim et al, 2010;Fabian et al, 2009).…”
Section: Fatty Acid Distillatementioning
confidence: 99%
“…Several methods have been proposed to recover phytosterols from the deodorizer distillate VerleyenVerhe, 2001;Kasim et al, 2010;Fabian et al, 2009). The byproduct obtained through physical refining has a higher FFA content than that obtained by chemical refining (El-Mallah et al, 2006).…”
Section: Fatty Acid Distillatementioning
confidence: 99%
See 1 more Smart Citation
“…The results presented showed that ESG were present at concentrations that were more than ten times higher than that of SG (mean values for seven samples: 230 mg/kg ESG and 10 mg/kg SG). In 2006, El-Mallah et al [10] proved that SG and ESG were partially eliminated during refining, mostly at the neutralization and the deodorization steps. Indeed, the total concentrations of ESG and SG were high in the soapstocks, around 1100 and 6400 mg/100 g, and much lower in the deodistillates from soybean oil refining, between 400 and 900 mg/100 g.…”
Section: Introductionmentioning
confidence: 99%
“…According to Evans et al (2002), the tocopherol concentration in commercial oil depends on the steps and conditions used to convert the crude oil into an edible product; however, the individual relative concentration is not significantly changed. The relative concentration of the individual tocopherol is from 2 to 13% of α-tocol, from 1 to 5% of β-tocol, from 54 to 71% of γ-tocol and from 21 to 41% of d-tocol (Evans et al, 2002;El-Mallah et al, 2006;Carrão-Panizzi and Erhan, 2007). The individual relative value found for the α-tocol (15%) and for the d-tocol (17%) remained within the range reported by Schimidt and Pokorný (2005) (from 0.9 to 35% of α-tocol and 15 to 93% of d-tocol).…”
Section: Estimation Of the Uncertaintymentioning
confidence: 99%